Analisis Pengaruh Brand Image Dan Service Quality Terhadap Revisit Intention Dengan Customer Satisfaction Sebagai Variabel Intervening (Studi Kasus Pada AHASS Comal Abadi Motor) - Arif Hadi Prasetyo; Fitri Lukiastuti (Magister Manajemen STIE Bank BPD Jateng, 2022)
This study aims to analyze the effect of brand image on revisit intention, service quality on revisit intention, brand image on customer satisfaction, service quality on customer satisfaction, customer satisfaction on revisit intention and the mediating role of customer satisfaction on brand image with revisit intention and quality. service with the intention to revisit. The object of this research is AHHAS comal eternal motor. The characteristics of the sample are customers who have used service services at least twice. The sample used in this research is 100 respondents. The data analysis method used is SEM-PLS. The results of the study concluded that brand image has a positive and significant effect on revisit intentions, service quality has a positive and significant effect on revisit intentions, brand image has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on customer satisfaction and significantly to revisit intention, brand image has a positive and significant effect on revisit intention through customer satisfaction and service quality has a positive and significant effect on revisit intention through customer satisfaction